PERANAN FUNGSI PENGAWASAN SEBAGAI INSTRUMEN PENINGKATAN PELAYANAN PUBLIK PADA INSPEKTORAT KOTA KENDARI - Sarinah, Sarinah; Said, La Ode Agus; Rijal, Muh (Aspirasi: Jurnal Ilmiah Administrasi Negara, 2025)
This study aims to analyze the role of the supervisory function as an instrument for improving public services at the Inspectorate of Kendari City. In the context of decentralization and local governance, internal supervision has a vital role to encourage transparency, accountability, and service effectiveness. Through a descriptive qualitative approach, data were obtained from interviews, observations, and documentation, with key informants from the Inspectorate. The results show that the supervision implemented includes internal auditing, setting work standards, as well as measuring results and correcting deviations. This function has contributed to improved governance and improved services, although challenges remain in the implementation of recommendations and public participation. This research confirms the importance of supervision based on good governance values and suggests optimizing participatory supervision strategies and utilizing information technology for more contextual and sustainable supervisory effectiveness. The research findings emphasize that supervision is not only administrative but also strategic in encouraging continuous improvement and responsiveness to community needs. This research contributes academically by filling the literature gap related to supervision and the quality of public services at the local level, and offers practical recommendations for optimizing the role of the Inspectorate.Keywords: Supervisory Function, Public Service, Accountability, Inspectorate, Good Governance.